DIMENSI KARAKTER NABI IBRAHIM DALAM AL-QURAN DAN PENDEKATAN TEORI PENDIDIKAN KARAKTER THOMAS LICKONA - Otong Surasman (Universitas PTIQ Jakarta, 2023)
This research explains the character of the Prophet Ibrahim (AS) in the holy book Al-Quran, as a comparison material for a character theory presented by Thomas Lickona, according to which he can improve human life with ten characters. This research uses a qualitative approach by conducting an in-depth study of the text of the holy book Al-Quran as its main source, which is closely related to the character of the Prophet Ibrahim as. Apart from the holy book Al-Quran as the main reference, we also use tafsir literature to make it easier to understand the character of the Prophet Ibrahim as contained in the holy book Al-Quran. The aim of this research is to obtain actual and factual information regarding the study of the implementation of Thomas Lickona's understanding of the character model of Prophet Ibrahim (AS), then use it as a reference as the main principle in living life, so as to create a life full of love, security, peace and prosperity